Boolean Feedforward Neural Network Modeling of Molecular Regulatory Networks for Cellular State Conversion - Choo, Sang-Mok; Almomani, Laith M.; Cho, Kwang-Hyun (Frontiers in Physiology, 2020)
The molecular regulatory network (MRN) within a cell determines cellular states and transitions between them. So, modeling of MRNs is crucial, but this usually requires extensive analysis of time-series measurements which is extremely difficult to obtain from biological experiments. However, single cell measurement data such as single cell RNA-sequencing databases have recently provided a new insight into resolving this problem by ordering thousands of cells in pseudo-time according to their differential gene expressions. Neural network modeling can be employed by using temporal data as learning data. In contrast, Boolean network modeling of MRNs has a growing interest as it is parameter-free logical modeling and thereby robust to noisy data, while still captures essential dynamics of biological networks. In this study, we propose Boolean feedforward neural network (FFN) modeling by combining neural network and Boolean network modeling approach to reconstruct a practical and useful MRN model from large temporal data. Furthermore, analyzing the reconstructed MRN model can enable us to identify control targets for potential cellular state conversion. Here, we show the usefulness of Boolean FFN modeling by demonstrating its applicability through a toy model and biological networks.